The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1515/znc-2010-11-1210
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Long-Chain n-Alkane-Degrading Strain, Dietzia sp. E1

Abstract: The complex [Cu(en) 2 (H 2 O)](sy) 2 (en)(H 2 O) 2 has been synthesized and characterized by its electronic and vibrational spectra. The molecular structure of the complex has been determined by X-ray diffraction methods. The complex crystallizes in the orthorhombic space group Pnma with unit-cell parameters a = 10.7236 (5), b = 20.4660(10), c = 14.4523(11)Å and Z = 4. In the cation, the Cu(II) ion has a distorted square pyramidal coordination with two bidendate (en) ligands forming the basal plane and a H 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Many microbial species were used by many researchers to degrade long-chain alkanes like B. stearothermophilus, Acinetobacter sp., B. thermoleovorans, G. kaustophilus, Dietzia sp., B. licheniformis, etc. (Sorkhoh et al 1993;Sakai et al 1994;Kato et al 2001;Sood and Lal 2008;Bihari et al 2010). However, the removal efficiency of the different isolates varied due to their action mechanisms on degradation of pollutants, substrate concentrations and their bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Many microbial species were used by many researchers to degrade long-chain alkanes like B. stearothermophilus, Acinetobacter sp., B. thermoleovorans, G. kaustophilus, Dietzia sp., B. licheniformis, etc. (Sorkhoh et al 1993;Sakai et al 1994;Kato et al 2001;Sood and Lal 2008;Bihari et al 2010). However, the removal efficiency of the different isolates varied due to their action mechanisms on degradation of pollutants, substrate concentrations and their bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication showed that Dietzia sp. E1 could degrade n-alkanes with the chain length ranging from C6 to C30 (Bihari et al, 2010). In addition, Dietzia strains have been reported to degrade aromatic compounds, including naphthalene (von der Weid et al, 2007), phenanthrene (Al-Awadhi et al, 2007), benzoate (Maeda et al, 1998), carbazole, quinoline, fluoranthene (Kumar et al, 2011) and toluene (von der Weid et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, only the gene encoding alkanes terminal monooxygenases 33 were amplied from Dietzia sp. ; 16,17 the gene encoding polycyclic aromatic groups dioxygenases 34 has not yet been reported from Dietzia sp. More research is needed to answer this question (Fig.…”
Section: Biodegradation Of Extra-heavy Oilmentioning
confidence: 99%
“…E1 has an excellent ability to degrade C12 to C38 n-alkanes, 16 Dietzia sp. DQ12-45-1b grows on a wide range of n-alkanes (C6-C40), aromatic compounds and conventional crude oil.…”
mentioning
confidence: 99%